Effect of Pea Flours with Different Particle Sizes on Antioxidant Activity in Pan Breads. Issue 5 (15th June 2017) - Davies‐Hoes, Lisa D.; Scanlon, Martin G.; Girgih, Abraham T.; Aluko, Rotimi E.
Abstract : Pulses are good sources of vitamins and minerals as well as antioxidants. Current literature supports a role for antioxidants in reducing oxidative damage associated with many health disorders, including cardiovascular disease and cancer. The effects of substitution of 10% (w/w) yellow whole or split pea flour (various particle sizes) in white wheat flour (Canadian Wheat Red Spring) on the phenolic and antioxidant activity of the leavened bread were examined. Antioxidant activity was evaluated with four assays, which included 1, 1‐diphenyl‐2‐picrylhydrazyl (DPPH) radical scavenging, ferric reducing antioxidant power (FRAP), metal chelation (MC), and superoxide (SO) radical scavenging assays. The bread samples had reduced DPPH (5–11% scavenging activity) and MC (5–10% scavenging activity) values compared with their respective raw flours. Decreased activity in both the DPPH and MC assays can be attributed to a reduction in the antioxidant capacity in the bread samples owing to dilution with white wheat flour. The MC values for bread samples showed little variability between the yellow whole and split pea flours (8–10% scavenging activity for yellow whole and 9% for split pea flours), which suggests that the antioxidant activity of bread samples is not dramatically affected by the seed coats. Most pea fractions increased the FRAP scavenging activity and decreased the SO scavenging activity values for the bread samples compared with their respective raw flours. We conclude that thermal processing enhanced the antioxidant activity of the bread samples, limiting the dilution effect associated with flour addition during dough make‐up.